Electrostatic-attraction-induced high internal phase emulsion for large-scale synthesis of amphiphilic Janus nanosheets. Issue 9 (11th January 2019) - Luo, Dan; Zhang, Fanghao; Zheng, Haotian; Ren, Zhensong; Jiang, Lili; Ren, Zhifeng
Abstract : A facile and scalable method to produce amphiphilic Janus nanosheets in large quantities was reported by interfacial reaction via generating a high internal phase emulsion. Abstract : We report a novel and scalable method to obtain amphiphilic Janus nanosheets in large quantities. By inducing electrostatic attraction using alkylamine with further tuned particle interactions, a highly stable water-in-oil high internal phase emulsion was generated while simultaneously performing single-side graphene oxide hydrophobization at the fluid interface.